Study on breast feeding and complementary feeding practices in rural mothers, Tamilnadu, India - Dr. Sivagamasundari Venugopal; Dr. Appandraj Srivijayan; Dr. Andy Karayalar Ramanath (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: Breast feeding of infants and young child is the natural and effective method which plays a major role in reducing the mortality of infants and under five children. There is significant reduction in the morbidities in the above age due to breast feeding. Inadequate knowledge and poor practices of breast feeding hinders the successful establishment of breast feeding. Objective: To determine the breast feeding and complementary feeding practices of mothers with children of age below 3 years from rural area who visited the outpatient department of paediatrics of karpagavinayaga institute of medical sciences, Kancheepuram, Tamilnadu. Materials and Methods: This was across sectional study done in hospital from 2017 September to 2018 January for a total duration of five months with structured questionnaire. Results: Exclusive breast feeding was given to 68.7% (n=76) of children. About 69.5% of the mothers had initiated the breast feeding within one hour of delivery. About 89.6% had given colostrum. Prelacteal feeds were given in 10.4%. Only 32.2% of mothers fed their babies on demand. Complementary feeding was started after six months by 80.9% mothers. Complementary feeding was started with homemade food by 49.6% of mothers. Conclusion: This study emphasis on education of mothers during their antenatal care, postnatal care and follow up care by obstetricians, paediatricians, residents and staff nurses regarding the importance of breast feeding and their advantages for better outcome in terms of reducing the morbidities and mortality in children below five years.